2020
DOI: 10.5858/arpa.2020-0102-ra
|View full text |Cite
|
Sign up to set email alerts
|

Primary Amyloidosis of the Genitourinary Tract

Abstract: Context.— Amyloidosis is caused by the deposition of misfolded proteins as insoluble eosinophilic material in the extracellular tissues of the body, leading to impairment of organ function. It can be systemic or localized. Localized genitourinary tract amyloidosis is rare and can be incidentally seen; however, in some cases, it can be the only presenting disease. Objective.— To review the clinical presentation and pathologic findings related to primary amyloidosis of the urogenital system and highlight some of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Primary localized amyloidosis in the ureter is a rare entity caused by extracellular deposition of insoluble fibrillary protein that may result in severe organ dysfunction. 1 Amyloidosis is classified based on the type of the involved amyloidogenic protein or based on tissue distribution. 1 Primary amyloidosis is usually defined as amyloid immunoglobulin light chain disease that could involve different organs typically affecting the skin, soft tissues, genitourinary system, respiratory system, and gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary localized amyloidosis in the ureter is a rare entity caused by extracellular deposition of insoluble fibrillary protein that may result in severe organ dysfunction. 1 Amyloidosis is classified based on the type of the involved amyloidogenic protein or based on tissue distribution. 1 Primary amyloidosis is usually defined as amyloid immunoglobulin light chain disease that could involve different organs typically affecting the skin, soft tissues, genitourinary system, respiratory system, and gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Amyloidosis is classified based on the type of the involved amyloidogenic protein or based on tissue distribution. 1 Primary amyloidosis is usually defined as amyloid immunoglobulin light chain disease that could involve different organs typically affecting the skin, soft tissues, genitourinary system, respiratory system, and gastrointestinal tract. Primary amyloidosis of the genitourinary tract is rare and most reported in the bladder and the prostate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because there was no systemic disease, no other predisposing factors, and no family history, the patient was diagnosed with primary localized lower urinary tract amyloidosis. Studies have reported that cystoscopy can detect multiple localized, slightly yellow polypoid disease, mucosal spotted hemorrhage, ulcer formation, [14] and papillary lesions. [15] However, these were not observed in the present case.…”
Section: Discussionmentioning
confidence: 99%